Knowledge Acquisition in GraPE (Grant Proposal Electronic Reviewing Assistant) - Mohd Yusoh, Zeratul Izzah; Shibghatullah, Abdul Samad; Bundy, Prof. Alan (2005)
The review of grant proposals is an important task in every academic field, but there exist no exact methodologies to help referees in doing this. The objective of this project is to build an expert system to assist beginner referees in this process. The system will be based on ERA (Electronic Referee Assistant), a knowledge-based advisor for Informatics research papers, and named GraPE (Grant Proposal ERA). GraPE aims to provide guidance to beginner referees to help them make better reviews and become better reviewers. As a fact, an expert system’s problem solving strategy relies on its knowledge. The knowledge has to be well defined, modelled, and represented in order to allow successful inference processes. This paper will describe the process of knowledge acquisition in GraPE, from the identification of knowledge sources to the knowledge modelling process.